Poetry, Religion, and Empowerment in Nigerian Lesbian Self-Writing - Unoma Azuah (African Journal of Gender and Religion (AJGR))
The Nigerian LGBT community is nearly invisible and mostly functions underground or through pseudonyms, in spite of the emerging visibility of queer writing in recent times. As a Nigerian lesbian woman and writer, in this article I seek to analyse some of my queer poems through an auto-ethnographic lens. While providing a brief history of contemporary Nigerian queer writings, their beginnings, their struggles, and their growth, even in the midst of their attacks, I will focus on and draw upon specific ex-periences as narrated in some of my poems, to explore how the religious constructions of my life and the lives of LGBT Nigerians can both limit and empower us. Through my experiences and the sharing of these involve-ments, I hope to be a part of the process that dismantles the religious block of homophobia that crushes us, and to reclaim religious language and imagery as a site of empowerment. Through my poetic testimonies, I liberate myself and, hopefully, my queer community.